Pickering HIPEs derived hierarchical porous nitrogen-doped carbon supported bimetallic AuPd catalyst for base-free aerobic oxidation of HMF to FDCA in water. (15th October 2020) - Guan, Wen; Zhang, Yunlei; Wei, Yanan; Li, Bing; Feng, Yonghai; Yan, Changhao; Huo, Pengwei; Yan, Yongsheng
Graphical abstract: Highlights: Nitrogen-doped carbon supported bimetallic AuPd catalyst was successfully synthesized. The obtained catalyst showed adjustable hierarchical pore and basicity. Catalytic oxidation of HMF to FDCA was carried out under base-free condition. The highest FDCA yield of 96.7% was achieved in water. Abstract: As an important renewable alternative to the production of petroleum-derived terephthalic acid, selective aerobic oxidation of biomass derivative 5-hydroxymethylfurfural (HMF) into high value-added 2, 5-furandicarboxylic acid (FDCA) is attracting increasing attention. Herein, a novel hierarchical porous nitrogen-doped carbon (NC) supported bimetallic AuPd catalyst was synthesized by Pickering high internal phase emulsions (Pickering HIPEs) templating method, subsequent carbonization and the sol-curing technique. By varying Pickering HIPEs parameter, nitrogen-doped content and the loaded AuPd nanoparticles, Aux Pdy /NC catalysts with adjustable porous structure and basicity were obtained. Benefiting from the synergistic effects of the high basicity of NC support and efficient bimetallic AuPd catalyst, tandem oxidation of HMF to FDCA reactions can be carried out under base-free condition in water, which makes the biomass transformation process environmental friendliness and economic. And the highest yield of FDCA at 96.7% was achieved under the optimal reaction conditions. Regeneration test revealed the obtained Aux Pdy /NC catalyst was recovered and reused at least five times without significant loss of catalytic activity. The present work offers a versatile strategy for developing nitrogen-doped carbon supported highly efficient bimetallic catalysts with hierarchical porous structure and adjusting basicity for a wide range of base-free catalytic oxidation in water.